A list of proposed standard levels for preparing the physics curriculum for the basic education stage, the second cycle (a field study): (دراسة ميدانية) (Journal of Hama University, 2022)
This study seeks to determine the largest possible number of standard levels required for the physics curriculum for the basic education stage in the Syrian Arab Republic. Objectives, content, means and activities, evaluation)? To achieve this goal, the researcher identified the largest possible number of the proposed standard levels, after referring to previous studies related to the subject and references to the current physics curriculum, as well as reviewing the references that tried to classify the standard levels.Then the researcher included these standard levels in a questionnaire addressed to a number of experts and specialists in this field to know their views on these proposed levels. Physics and Chemistry in (the field of output) (2) have two levels, and the number of indicators that fall under it is (21) indicators distributed on the two mentioned levels as follows: The first level falls under it (15) indicators, and the second level falls under it (6) indicators. B - In the field of goals: its number reached (7) levels, and the number of indicators that fall under it reached (32) indicators distributed on the mentioned levels.C - In the field of content, its number reached (3) levels, and the number of indicators that fall under it reached (22) indicators distributed on the mentioned levels. D - In the field of means and activities, the number of indicators that fall under it is (38) indicators distributed on the mentioned levels. E - In the field of evaluation, its number reached (3) levels, and the number of indicators that fall under it reached (12) indicators distributed over the mentioned levels.
Keywords: Standards - Physics Curriculum - Basic Education